Effect of chromium addition on the structural, morphological and magnetic properties of nano-crystalline cobalt ferrite system - Koseoglu, Yuksel; Oleiwi, Mousa Ibrahim Oleiwi; Yilgin, Resul; Kocbay, Abdullah N. (Elsevier Sci Ltd, 2012)
Nano-crystalline chromium doped cobalt ferrite powders have been synthesized by PEG assisted hydrotherrnal route. The structural, morphological and magnetic properties of the products were determined by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy and vibrating sample magnetometer (VSM). X-ray analysis showed that the samples were cubic spinel. SEM images reveal that the samples' surfaces exhibit well-defined crystalline nanoparticles of spherical shapes with small agglomeration. The addition of Cr3+ ions caused a decrease in the average crystallite size, magnetization and the coercive field of the sample. The observed decreases in saturation magnetization and coercivity are explained on the bases of exchange interactions. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Hydrothermal synthesis; XRD; Magnetic nanoparticles; Mn-Co spinel ferrites